Three-dimensional reconstruction of the orbital retrobulbar vasculature. (4th July 2022) - X. Texeira, Dominic; Cheung, Alison; Naveed, Hasan; J. Adds, Philip
ABSTRACT: Purpose: The retrobulbar orbital vasculature is known to be complex and variable between individuals. This study aimed to produce a method to map the retrobulbar vessels, to generate 3D reconstructions, to visualise and to improve our understanding of their complexity. Methods: Five human orbits donated under the Human Tissue Act (2004) were fixed in formalin, decalcified in 10% formic acid, and dehydrated in acetone at −20°C. Specimens were impregnated with epoxy resin, cured, and cut into 0.3 mm sections. Sections were stained with Gomori's trichrome stain, imaged, and reconstructed using 3D reconstruction software (BioVis3D, version 3.1). Results: The arterial system was reconstructed in all five specimens. The superior ophthalmic vein (SOV) and the central retinal vein (CRV) were reconstructed in four specimens. E12 sheet plastination showed excellent results for histological analysis at a macroscopic level; however, anatomical topology was not entirely preserved on a microscopic level. Gomori's trichrome stain gave excellent results in highlighting axial sections of the arterial walls and their tunics, including finer calibre vessels, thus allowing detailed reconstruction of the arterial vasculature. Miller's stain for elastin showed poor results in differentiating vessels from soft tissue; venous vasculature was poorly identified with both stains. Conclusions: This study provided a detailed anatomical model of the retrobulbar orbital vascular system, a method that can be used for further studies to form a database relating to the topography of the arterial system. These models may be employed for teaching, and possible surgery planning, for both trainees and ophthalmic surgeons.